Ayat-Ayat Pendidikan Inklusif: Model Pendidikan PAI Ramah ABK Berdasarkan Perspektif Tematik Qur’ani - Supriatin, Iit; Ismail, Dudi; Kania, Dewi; Anshori, Hanafi; Santoso, Muhammad Iqbal (Halaqa: Journal of Islamic Education, 2025)
Education for Children with Special Needs (CSN) in Indonesia continues to face various challenges, particularly in accessing inclusive and adaptive Islamic Religious Education (IRE). The integration of Qur’anic values through a thematic exegesis approach has not yet been fully optimized to support CSN learning. This study aims to formulate an inclusive IRE curriculum model based on relevant Qur’anic values. Using a qualitative method and thematic interpretation, the research analyzes selected Qur’anic verses alongside classical and contemporary exegeses. The findings reveal inclusive values—such as compassion, accessibility, respect for human dignity, and adaptability to limitations—reflected in QS ‘Abasa [80], al-Nūr [24], al-Ḥujurāt [49], al-Isrā’ [17], and al-Nisā’ [4]. The study proposes a model for an inclusive IRE curriculum and lesson plans (RPP) that are responsive to the needs of CSN. This research contributes to the academic discourse on inclusive Islamic education and provides practical insights for policy development at madrasahs and general education institutions. This study offers a novel integration of thematic Qur’anic exegesis into Islamic inclusive education design, with strategic implications for curriculum development and policy in religious and public education systems.